Orchomenos, Griechenland. »Berühmt wie nur irgendeine sonstige Stadt...« – neue Forschungen in Orchomenos. Projekt »STADT und MAUER in politischen und urbanistischen Umbruchsphasen des 4. Jahrhunderts v. Chr. in Mittelgriechenland« - Laufer, Eric (e-Forschungsberichte des DAI, 2022)
Since 2021 a research project at the DAI Athens is dedicated to fortifications and urban development in Central Greece during the 4th century BC. As part of this project new fieldwork was initiated in Boeotian Orchomenus. Its well preserved fortification system includes the main city’s circuit with diateichismata, the acropolis fortress and several extraurban defence structures, the functions and chronological sequence of which are not clear yet. A new survey of the fortification will hopefully contribute to a better understanding of Orchomenus‘ urban development in the classical and hellenistic period. The research is based on the new topographical map of the city (measured 1997–2000 by the DAI Athens) as well as new fieldwork started in autumn 2021.